Measuring kinematic changes of the foot using a gyro sensor during intense running - Shih, Y.; Ho, C.-S.; Shiang, T. Y. (Journal of Sports Sciences, 2014)
Gyro sensor has been used to measure foot pronation during running with reliable results in previous studies, and the signals were not affected by the vibration of heel strikes. The purpose of this study was to observe the kinematic changes of the foot during intense running using a 3-axis gyro sensor. Fifteen male participants (average age: 24.5 ± 1.7 years; mean height: 174.1 ± 3.3 cm; mean body weight: 71.0 ± 5.5 kg) were recruited in this study. Foot kinematic changes were observed in 30-min intense running protocols. The comparisons of the signals from gyro and motion analysis system were also performed to determine the accuracy of the gyro and showed positive results. In the main experiment, the ankle range of motion (ROM) in the frontal plane, measured using a motion system, showed a significant increase over time. Accordingly, peak angular velocity in the frontal plane also showed a significant increase. The correlation between ankle ROM and peak angular velocity in the frontal plane is significantly high (r = 0.975). Moreover, peak angular velocity in the frontal plane is also significantly correlated with both rate of perceived exertion (RPE) (r = 0.911) and heart rate (r = 0.960). This study concluded that an alarm system for foot kinematic changes related to running injuries can be built based on the peak angular velocity of the foot in the frontal plane.